Analysis and simulation of an Urban-Industrial Sustainable Energy Community: A use case in San Juan de Mozarrifar using photovoltaic energy - Víctor Caballero; Alan Briones; Adriana Coca-Ortegón; Aitor Pérez; Blanca Barrios; Miquel de la Mano (Energy Reports, 2023)
Although Spain is the country in the European Union with the highest photovoltaic generation potential, the number of solar energy community initiatives remains relatively low. Spain has more than 6,000 industrial parks, and most require improvements concerning their conservation and services. The integration between industrial parks and urban areas in Spain has plausible benefits. This work analyzes and simulates an urban-industrial sustainable energy community in San Juan de Mozarrifar (Spain), which comprises an urban area and an industrial park area. We classify the energy community using taxonomies found in the literature and the concept of Urban-Industrial Symbiosis considering photovoltaic energy; then, we analyze and estimate the electricity generation potential from photovoltaic panels in both the urban and industrial areas; finally, we simulate the energy community and propose improvements to increase its self-sufficiency. We also highlight that the industrial sector presents a great opportunity to install renewable energy resources and provide renewable energy to the co-located urban area; and adding photovoltaic panels to public buildings may be a strategy to meet residential energy demand, especially for households that do not have photovoltaic installations for self-consumption.